Sport and Social Regulation in the City: The Cases of Grenoble and Sheffield - Dulac, Christine; Henry, Ian (Loisir et Société / Society and Leisure)

(untitled) (Presses de l’Université du Québec, 2001)
AbstractThis article seeks to redress the dearth of comparative urban sports policy literature, undertaking an historical analysis of the development of sports policy in a French and a British city (Grenoble and Sheffield) from the late 1960s to the end of the century. Both of the cities, though very different in political, cultural and economic terms, have given considerable prominence to, and have significantly changed the nature of, local sports policy. The article employing an approach drawn from regulation theory identifies and explains similar trends evident in both cities. There is in both cases a “structured coherence” between the hardware (spectacular sporting facilities / events / sporting spectacle), organisational forms (commercialised, de-bureaucratised operations) and the dominant sets of social relations (increasingly market relations) which characterise their emergent sports policy systems and which systematically privilege market over social interests, reflecting post-Fordist policy goals despite very different political, institutional and structural contexts.